2022
DOI: 10.1242/jeb.243216
|View full text |Cite
|
Sign up to set email alerts
|

2D and 3D visualizations of archosaur jaw muscle mechanics, ontogeny and phylogeny using ternary diagrams and 3D modeling

Abstract: Comparing patterns of performance and kinematics across behavior, development and phylogeny is crucial to understand the evolution of complex musculoskeletal systems such as the feeding apparatus. However, conveying 3D spatial data of muscle orientation throughout a feeding cycle, ontogenetic pathway or phylogenetic lineage is essential to understanding the function and evolution of the skull in vertebrates. Here, we detail the use of ternary plots for displaying and comparing the 3D orientation of muscle data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 85 publications
3
10
0
Order By: Relevance
“…Although the focus of this study was a comparison among taxa, smaller extant crocodylians had more dorsoventrally oriented muscles. This matches findings from an ontogenetic sample of A. mississippiensis (Cost et al, 2022). Heterochronic shifts are a common source of evolutionary shape change, and have been suggested to underlie other aspects of crocodylian skull shape and functional evolution (Gignac & O'Brien, 2016; Morris et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Although the focus of this study was a comparison among taxa, smaller extant crocodylians had more dorsoventrally oriented muscles. This matches findings from an ontogenetic sample of A. mississippiensis (Cost et al, 2022). Heterochronic shifts are a common source of evolutionary shape change, and have been suggested to underlie other aspects of crocodylian skull shape and functional evolution (Gignac & O'Brien, 2016; Morris et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…These data enable further exploration into muscle mechanics by combining estimates of muscle attachments, muscle volumes and even muscle architecture (Figures 7, 8). We have previously shown that 3D muscle resultants can be accurately derived from 3D muscle attachment mapping and frustum‐based volume estimates to estimate bite forces in Alligator mississippiensis (Sellers et al, 2017) and that these muscle resultants can be used to track changes in cranial performance among sauropsids (e.g., Cost et al, 2019; Wilken et al, 2019; Wilken et al, 2020; Cost et al, 2022) and during suchian evolution (Sellers et al, 2022).…”
Section: D Jaw Muscle Resultants and Muscle Architecturementioning
confidence: 99%
“…Here, we used simple and complex polyhedrons to estimate volumes of the jaw muscles in two different ways. Sellers used Strand7 (G1D Computing Pty Ltd, Sydney, Australia) to map surface areas of muscles reflecting their bony attachments (sensu Grosse et al, 2007; Davis et al, 2010; Sellers et al, 2017, Cost et al, 2020; Cost et al, 2022; Sellers et al, 2022) and then the centroids and surface areas of the origins and insertions were used to calculate the volume of a frustum (Sellers et al, 2017), a relatively simply shape. Meanwhile, Lautenschlager employed their outline & fill (O&F) method, where, using Avizo (Thermo Fisher Scientific), the estimated boundaries of muscle attachments were marked and connected by a series of narrow cylinders (Lautenschlager 2013).…”
Section: Segmentation and Volumetric Estimatesmentioning
confidence: 99%
“…non‐skeletal) AAs; a reminder that attachment type (bony, tendinous, aponeurotic) is critical for PCSA:AA estimation. Their subsequent studies have expanded on these concepts and methods (Cost et al, 2022 ; Sellers et al, 2022 ). Bates and Falkingham ( 2012 ) (also see Gignac & Erickson, 2017 ) adopted a similar 3D modelling approach for estimating bite forces in a human and the archosaurs Alligator (juvenile and adult models) and Tyrannosaurus , estimating PCSAs from muscle volumes spanning approximate AAs; and again obtaining reasonable matches of empirical bite force data from humans and Alligator ; although PCSA estimates tended to have 5%–12% error (22% maximum) investigated with sensitivity analyses.…”
Section: Introductionmentioning
confidence: 99%
“…we would know exactly the geometry desired). Again, we calculated the resulting areas in Meshlab.Subsequently, we made PCSA calculations following standard muscle architecture techniques (e.g Cuff et al, 2016). and equation1:where m musc = muscle mass (g), Θ = pennation angle relative to the muscle's line of action, l fasc = fascicle length, and d = muscle density (=1060 kg m −3 ;Mendez & Keys, 1960).…”
mentioning
confidence: 99%